Can ESG increase firm value in the banking institution and financial services in Malaysia? An insight from social norm theory - Mohd Ashari Bakri; Mohamad Isa Abd Jalil; Zakiah Hassan (Universal Publishers, 2022)
This paper aims to ascertain the impact of environmental, social and governance (ESG) on Malaysian banking institutions and financial services. The study examined 24 firms from the banking institution and financial services obtained from DataStream. The study used OLS, random effect and fixed effect analysis with robust standard error. To ensure robust result, the study uses two stages lease square to solve for potential endogeneity concerns. The finding reveals that ESG increase firm value significantly in all analysis. The study also discovered that social pillar score negatively moderates ESG and firm value. Research limitations/implications: The data is only limited to Malaysia’s banking institution and financial services. Thus the results may not be extrapolated into other industries. A manager should promote the ESG agenda to obtain a better firm valuation among investors, especially those concerned with the ESG agenda. By applying the perspective from social norm theory, the study shows that empowering social responsibility disclosure (create positive credibility to investors) significantly adds value within banking institutions and financial services firms in Malaysia. The study also discovered that the social pillar has a significant moderating effect on ESG and firm value relationships.